Analysis of the effect of fraud triangle dimensions, selfefficacy, and religiosity on academic fraud in accounting students - Irene Nia Melati; R Wilopo; Indah Hapsari (The Indonesian Accounting Review, 2018)
Academic fraud is a bad habit done by students, particularly the college students. This bad habit includes cheating, opening the answer key during the test, or involving teamwork on individual homework. This academic fraud occurs because of several factors. This research aims to analyze the factors that influence academic fraud consisting of fraud triangle dimensions (pressure, opportunity, and rationalization), self-efficacy, and religiosity. Respondents of this research are the accounting students at STIE Perbanas, Surabaya. Respondents were collected using convenience sampling method. This research is a quantitative research conducted using a multiple regression analysis. The results of this research show that the variables of pressure and rationalization have an effect on academic fraud, while the variables of opportunity, self-efficacy, and religiosity have no effect on academic fraud.